Akibat Hukum Program Pendaftaran Tanah Sistematis Lengkap (PTSL) bagi Kesejahteraan Ekonomi Masyarakat - Arina Jazaiyatun Hasanah (Jurnal Hukum Lex Generalis, 2022)
The Systematic Land Registration Program (PTSL) aims to provide legal certainty and legal protection for community land rights. Therefore PTSL is considered important in people's lives which will provide legal certainty to the land they own in the hope that after having the land certificate the community can make the best use of their land and get legal protection for community land rights which can then help the government to improve welfare Public.